Masculinity, race and national identity: representations of non-Japanese men’s speech in contemporary Japanese novels - Suzuki, Satoko (Gender and Language, 2020)
Language ideologies have been of central concern to the study of Japanese language, gender and society. Many scholars have researched ideologies surrounding representations of Japanese women’s speech; however, investigations of representations of men’s speech have been limited. This study contributes to filling this gap through the analysis of non-Japanese male characters found in contemporary Japanese novels. The article reveals that authors assign strongly masculine expressions to their East Asian characters much more frequently than to their white characters and argues that these differentiated representations of non-Japanese male characters’ speech reproduce and are influenced by ideologies concerning cultural nationalism, racial determinism, class and sexuality. Linguistic data are presented that both unsettle the constructed image of Asian males as asexual beings and question the historically assumed relationship between gendered language and authenticity.
Keywords: arts; asie; cours; discipline; histoire et politique; japon; lin2685; linguistique; masculinité; premier cycle; représentation des hommes; régions géographiques; sciences humaines; sofia; thématiques; études littéraires

Ru - Thúy, Kim (Libre Expression,une compagnie de Quebecor Media, 2009)
« "Le paradis et l'enfer s'étaient enlacés dans le ventre de notre bateau. Le paradis promettait un tournant dans notre vie, un nouvel avenir, une nouvelle histoire. L'enfer, lui, étalait nos peurs : peur des pirates, peur de mourir de faim, peur de s'intoxiquer avec les biscottes imbibées d'huile à moteur, peur de manquer d'eau, peur de ne plus pouvoir se remettre debout, peur de devoir uriner dans ce pot rouge qui passait d'une main à l'autre, peur que cette tête d'enfant galeuse ne soit contagieuse, peur de ne plus jamais fouler la terre ferme, peur de ne plus revoir le visage de ses parents assis quelque part dans la pénombre au milieu de ces deux cents personnes." Ru est le récit d'une réfugiée vietnamienne, une boat people dont les souvenirs deviennent prétexte tantôt à l'amusement, tantôt au recueillement, oscillant entre le tragique et le comique, entre Saigon et Granby, entre le prosaïque et le spirituel, entre les fausses morts et la vraie vie. »-- Quatrième de couverture.
Keywords: amériques; approches et analyses; arts; asie; boat people; canada; cours; discipline; histoire et politique; immigration; lit3220; littérature; premier cycle; québec; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; vietnam; écriture des femmes*; études littéraires